Looking east through the colonnade of the Agricultural Building toward the Manufactures Building, Alaska-Yukon-Pacific Exposition, Seattle, Washington, 1909 - University of Washington Libraries. Special Collections Division (1909)
Caption on image: Looking East through Colonnade of the Agricultural Building, Alaska-Yukon-Pacific Exposition, Seattle, Wash., 1909 Publisher: Post Card Co. Printed on verso: 5365 PH Coll 78.81 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number